Evaluation of abnormal uterine bleeding by transvaginal sonography, sonohysterography and correlation with endometrial histopathology - Sinha, Parul; Gupta, Uma; Waris, Basma; Dubey, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) in reproductive-age women is common, leading to one-third of outpatient visits by this population and this proportion crosses the two-third threshold in peri or post-menopausal group. Annually 5-10% of women of reproductive age seek medical care for AUB, which negatively impacts quality of life. The aim of the present study was to study the role of transvaginal sonography (TVS) and sonohysterography (SHG) in abnormal uterine bleeding. Methods: The present study was carried out at Department of Obstetrics and Gynaecology, Era’s Lucknow Medical College, Lucknow in collaboration with Department of Radiology and Pathology, Era’s Lucknow Medical College, Lucknow. It was a prospective study carried out over a period of 1 year. Detailed history regarding their present complaints, menstrual history along with thorough examination was noted on the proforma designed for the study. Those with active and heavy bleeding underwent TVS and D&C for diagnostic and therapeutic purposes in the same sitting. However others without active bleeding underwent TVS, SIS in mid cycle and D&C in premenstrual period. Results: The present study was carried out at Department of Obstetrics and Gynaecology, Era’s Lucknow Medical College, Lucknow in collaboration with Department of Radiology and Pathology, Era’s Lucknow Medical College, Lucknow. It was a prospective study carried out over a period of 1 year. Detailed history regarding their present complaints, menstrual history along with thorough examination was noted on the proforma designed for the study. Those with active and heavy bleeding underwent TVS and D&C for diagnostic and therapeutic purposes in the same sitting. However others without active bleeding underwent TVS, SIS in mid cycle and D&C in premenstrual period. Conclusions: The findings in present study show a relative supremacy of SIS over TVS in diagnosis of uterine abnormalities in cases of abnormal uterine bleeding.